The Effect of Applying Model Problem Based Learning Against Sub-theme Learning Outcomes “Bangga Terhadap Daerah Tempat Tinggalku” - Siti Yulia Sindi; Suhendra Suhendra; Rini Sri Indriani (Journal of Education and Teaching Learning, 2023)
The Influence of the Application of Problem Based Learning Model on Learning Outcomes of the Proud Subtheme of the Area I Live in. This research is a quasi-experimental research. This study has a purpose, namely to determine the effect of the application of the Problem Based Learning model on the learning outcomes of the proud sub-theme of the area where I live. This research was conducted at the Cibodas 02 State Elementary School, Bogor Regency, Class IV-A and IV-B in the month of May in the even semester. Calculation of the N-Gain Model Problem Based Learning pretest is worth 48, the average value is 73, and the posttest score is 86 with the completeness criteria being 89%, the N-Gain Conventional Model pretest is worth 48, the average value is 53, and the posttest value is 78 with the following criteria: completeness is 71%. The results of hypothesis testing that have been carried out state that Ho is rejected and Ha is accepted, because the calculation results obtained tcount 6.1162 > ttable 2.00488.